Orientalism : A Reader - Edited by; A.L. Macfie (Edinburgh Edinburgh University Press, 2000)
"In the period of decolonization that followed World War II, a number of scholars, mainly Middle Eastern, launched a sustained assault on Orientalism, the theory and practice of representing the "East" in Western thought, accusing its practitioners of misrepresentation, prejudice and bias. An intense debate ensued, involving not only Orientalists but historians, sociologists, anthropologists, literary critics, scholars of cultural studies and gender studies as well as the news media. -- Orientalism: A Reader provides ... a selection of key readings from this debate, covering a range of areas including myth, imperialism, the cultural perspective, Marxist interpretation and feminist approaches. The aim is to introduce the origins and character of the debate on Orientalism, providing a useful overview of a controversial and problematic concept from a multidisciplinary perspective. Coverage begins with late 19th-century material from thinkers such as Hegel and Marx, and moves through extracts from Nietzsche, Gramsci and Foucault to contemporary work from, Brian Turner, John Mackenzie and Edward Said."
Include Bibliography and Acknowledgements
Keywords: Orientalism -- Asia -- Middle East -- Study skills -- Public opinion, Western -- East and West